Islam Transmigran: Studi Integrasi Budaya Masyarakat Transmigrasi di Sumatera Barat - Kohar, Wakidul; Hasan, Yummil (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2018)
The dynamics of religious encounter in Minangkabau with this culture are sometimes manifested as resistance from the local culture towards Islam and foreign culture (as a new culture), but many of them can blend without having to show resistance from one element, both because of the original cultural factors is dynamic and adaptive to the new culture and because of the adjustment made by Islam and foreign culture which at that time was positioned as a new culture. Almost all religions cannot be separated from the culture in which religion arises and develops. The acceptance of Islam and foreign cultures in the Minangkabau community certainly passed through various stages of the process, such as the process of acculturation, assimilation, diffusion, and so on. Islamic encounters and various cultures with adat in Minangkabau in transmigration areas are expressed in several forms: first, Islam and various kinds of culture can be integrated into socio-cultural-religious expressions, thus giving birth to an assimilative Islamic tradition. Second, Islam and cultural are not integrated, but also do not trigger conflict and conflict, resulting in an acculturative Islamic tradition. Third, varied Islam and cultural contradict each other, whether or not they cause conflict or not.